The Relationship Of Balance, Agility And Concentration To Dribbling Skills In Football Players - Tantowi, Umam; Arisman, Arisman; Hendriyanto, Ferri; Suhermon, Suhermon; Siska, Siska; Tofikin, Tofikin; Indah, Debby (DEPARTEMEN KESEHATAN DAN REKREASI FAKULTAS ILMU KEOLAHRAGAAN, 2025)
The problem with this research is that the football dribbling skills of Persiraja Fc football club players are still lacking. The aim of this research is to find out the relationship between balance, agility and concentration on soccer dribbling ability. This research is quantitative correlational, the population and sample in this research are 24 people. The sampling used was total sampling. This research instrument includes a standing stroke test for balance, an agility test using the Illinois agility test, a concentration test using the concentration grid exercise, and a ball dribbling test using the ball dribbling test. The data analysis technique uses the Spearman rho correlation analysis technique and multiple correlation using the α = 0.05 level. The results of the research are 1) There is no significant balance relationship with the dribbling ability of Persiraja Fc club players with the results of data analysis obtained t_(count ) 0.51< t_table 1.71 2) There is a significant relationship of agility with the dribbling ability of Persiraja Fc club players with the results of the data analysis obtained t_(count )2.29>t table 1.71 3) There is no significant balance relationship with the dribbling concentration of Persiraja Fc club players with the results of the data analysis obtained t (count )1.59<t table 1, 71 4) There is a significant relationship between balance, agility, concentration on the dribbling ability of Persiraja Fc club players and the results of data analysis obtained F_count 3.07>F_table 1.98.